(untitled) (Research, Society and Development, 2021)
Inadequate land use contributes to the intensification of land degradation, according to the United Nations Food and Agriculture Organization (FAO). 33% of the world’s soils are degraded. Among the main problems, erosion, especially water erosion, is considered by many authors as the biggest problem related to soil degradation. The correct use of the soil, with the adoption of conservationist management systems is fundamental for the maintenance of the soil and consequently for the food production. Thus, the objective of this work was to verify, through theoretical classes and practical essays, the learning efficiency of integrated high school students of the Agricultural Technical Course of the Federal Institute of Amapá, IFAP, of the Porto Grande Agricultural Campus, about the importance of soil conservation. The study was developed in order to evaluate the difficulties and potentialities of the subjects involved in the teaching and learning process on the theme of soil conservation. We sought to understand the students’ perceptions about the lectures and practical essays on the importance of soil, soil types and the impacts of anthropic influence on soil degradation. The lectures together with the practical essays were efficient, in the understanding by the students, about the importance of soil conservation, being methodologies that stimulated curiosity and experimentation in the students.